If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -1x) = 4x (3 * 4 + -1x * 4) = 4x (12 + -4x) = 4x Solving 12 + -4x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -4x + -4x = 4x + -4x Combine like terms: -4x + -4x = -8x 12 + -8x = 4x + -4x Combine like terms: 4x + -4x = 0 12 + -8x = 0 Add '-12' to each side of the equation. 12 + -12 + -8x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -8x = 0 + -12 -8x = 0 + -12 Combine like terms: 0 + -12 = -12 -8x = -12 Divide each side by '-8'. x = 1.5 Simplifying x = 1.5
| 11m=-33+8z | | 2(2x+1)+(-3)+(-6)= | | 2(2x+1)+(-3)+(-6)=x | | 2n-7=27 | | a+2b+3c=13 | | 5a+56=7(8) | | 8x-3x-7=38 | | -5(3x+1)-14=10(x+2)-2x+1 | | 4x-2=13-2x | | -5(3x+1)=10(x+2)-2x+1 | | 8-4m+5-6m= | | 37=X+3X-4 | | 15c-8c=20c-13 | | Y=4-3(1.33) | | 4n/5-1/5=2n/5 | | 2.95*1=4x | | 11.97=x/1.2 | | 2.95*4=1x | | 3(2x+1)=7x | | (2x-pi/4)=-1 | | 3y+8=2y-2 | | 20=4y+8x | | 6g+2g+g=81 | | 12x+4y-6=0 | | -16t^2+24t+30=0 | | ln(60y+100)-ln(100)=-(ln(180x-30)-ln(30)) | | 3(2+x)=8(x-2) | | 8+7g=15 | | -13u-16=2-14u | | 4r+8p-2r+5p= | | 16n=-17+15n | | 5*5=30 |